Exploring collaborative learning, research and action in public service reform : Aberdeenshire health and social care change fund Beyond Action Learning initiative /: Aberdeenshire health and social care change fund Beyond Action Learning initiative. (January 2017) - Soutar, Fiona; Warrander, Jane; Dr, Henderson, James
No abstract available